Potensi Ikan di Danau Padong Pangeran Pati Sebagai Sumber Belajar Biologi - Putri Dwi Setya Ningsih; Eko Dewantoro; Mahwar Qurbaniah (Postgraduate, University of Mataram, 2025)
Several areas in Sanggau Regency have fish diversity that has the potential to be developed as a biology learning resource, one of which is Lake Padong Pangeran Pati. This study aims to identify the types of fish found in the lake and analyze their potential and suitability as a biology learning resource. The method used is descriptive qualitative with purposive sampling techniques. The analysis was carried out through direct observation and expert assessment of the relevance of the fish potential to biology subject matter at the junior and senior high school levels. The results showed that Lake Padong has fish diversity relevant to several biology topics such as classification of living things, ecology, biodiversity, as well as reproductive systems and animal tissue, with a feasibility percentage of 69.43%. This potential is considered feasible to be used as an alternative learning resource. The study recommends utilizing local potential in contextual learning to enhance students' understanding of biological concepts.